DIFFERENCES IN CLASS XI STUDENTS' LEARNING RESULTS IN SOCIOLOGY SUBJECTS USING THE WORD SQUARE LEARNING MODEL WITH THE LECTURE LEARNING MODEL SMA NEGERI 4 JEMBER - YETTY NORMANINGSIH (Journal of Education Technology and Inovation, 2022)
The Sociology learning process carried out at SMA Negeri 4 has problems related to the learning process which still uses the lecture method, so students tend to be passive in the classroom. This resulted in less than optimal student learning outcomes. One alternative to encourage students to have better learning outcomes is the application of the Word Square learning model. The population in this study were students of class XI IPS SMA Negeri 4 Jember. The research sample was class XI IPS-2 as the experimental group and class XI IPS-1 as the control group with 37 students each. Sampling using the Cluster Random Sampling technique. The data collection methods used include: tests and documents. The results of the research from the t-test 2,414 > 1.67, there are differences in learning outcomes between the experimental group using the Word Square learning model and the control group using the lecture learning model. The average learning outcome of the experimental group is 78.23, which is greater than that of the control group, which is 74.02, this means that the learning outcome of the experimental group is greater than that of the control group. From the results of observations of students on average, it shows that student learning outcomes have increased. This means that students like the learning process that applies the Word Square learning model in the learning process